Wear of Wood Polymer Composite for Journal Bearing Materials - Sinin Hamdan; Mohd. Abdul Mun’aim; Mohd. Idrus; Md. Rezaur Rahman; Nurul Faziha Ibrahim; Md. Saiful Islam (Masyarakat Peneliti Kayu Indonesia, 2010)
Wood is broadly used for automotive parts, construction materials, and equipment for leisure-time amusement; however, its application for journal bearings has been restricted due to its low strength and poor tribological characteristics. In this work, Falcataria moluccana or Paraserianthes moluccana, locally known as Batai wood, which have low density and high porosity were impregnated with motor oil, (SL/CF 15W-50), hexamethylene diisocyanate, and diphenylmethane-4, 4’-diisocyanate to improve their compressive strength and tribological characteristics. A vacuum-pressure method was used to impregnate the wood specimens. From scanning electron microscopy (SEM) analysis, wear test, and compression test results, it was found that the hexamethylene diisocyanate was a promising material to improve the physical properties of wood for journal bearings.